2019
DOI: 10.5194/acp-2019-130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogenic and Anthropogenic sources of Arctic Aerosols

Abstract: <p><strong>Abstract.</strong> There are limited measurements of the chemical composition, abundance, and sources of black carbon (BC) containing particles in the high Arctic. To address this, we report 93 days of Soot Particle Aerosol Mass Spectrometer (SP-AMS) data collected in the high Arctic. The period spans from February 20th until May 23rd 2015 at Villum Research Station (VRS) in Northern Greenland (81°36' N). Particulate sulfate (SO&am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 56 publications
(105 reference statements)
5
15
1
Order By: Relevance
“…In general, it is known that particularly Arctic spring aerosol is acidic throughout the troposphere (Fisher et al, ). Specifically for the vicinity of VRS, it was recently described that acidic aerosol is present in spring, explained by high amounts of sulfuric acid (Nielsen et al, ). On the other hand, κ values in literature, such as those discussed above, indicate a rather high content of organic aerosol.…”
Section: Resultsmentioning
confidence: 99%
“…In general, it is known that particularly Arctic spring aerosol is acidic throughout the troposphere (Fisher et al, ). Specifically for the vicinity of VRS, it was recently described that acidic aerosol is present in spring, explained by high amounts of sulfuric acid (Nielsen et al, ). On the other hand, κ values in literature, such as those discussed above, indicate a rather high content of organic aerosol.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we showed how the sub-micrometer ambient particle concentration, measured by a Soot Particle Aerosol Mass Spectrometer (SP-AMS), and its chemical composition changed from a mean of 2.3 μg m − 3 in February at the onset of the Arctic Haze period, to 1.2 μg m − 3 in May (Nielsen et al, 2019). In this period, biogenic sources became relatively more important than anthropogenic sources.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of chemical composition, sulfate (SO 4 2− ) was the major component, comprising 66% of the non-refractory PM 1 , followed by organics, accounting for 24% of PM 1 . Using Positive Matrix Factorization (PMF) (Ulbrich et al, 2009;Zhang et al, 2011) and more specifically the PMF Evaluation Tool Software (PET, v2.08D; available online at http://cir es1.colorado.edu/jimenez-group/wiki/index.php/PMF-AMS_Analy-sis_Guide), Nielsen et al (2019) found that three factors explain the observed organic Aerosol (OA). First, Hydrocarbon-like Organic Aerosol (HOA, anthropogenic), characterized by hydrocarbon fragments from chemically reduced organic emissions and attributed to primary combustion sources of liquid, usually mostly fossil origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of Arctic Haze (Quinn et al, 2007) is largely determined by variety of process. Aerosol with Brown and Black Carbon is produced to a minor extend by the oxidation of natural sand anthropogenic missions of hydrocarbons and to a major extend by fires/ biomass burning (Heintzenberg et al, 1981;Quinn et al, 2007;Nielsen et al, 2019). Black carbon has been widely discussed in the literature (Hansen and Nazarenko, 2004;Ramanathan and Carmichael, 2008;Bond et al, 2013;Jacobi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%